On the Connection Between the Spectral Difference Method and the Discontinuous Galerkin Method (Communications in Computational Physics, 2011)
In this short note we present a derivation of the Spectral Difference Schemefrom a Discontinuous Galerkin (DG) discretization of a nonlinear conservation law.This allows interpretation of the Spectral Difference Scheme as a particular discretizationunder the quadrature-free nodal DG paradigm. Moreover, it enables identificationof the key differences between the Spectral Difference Scheme and standard nodal DGschemes.